PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS GAMES UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PROSEDUR KERJA ANIMASI 2D MATA PELAJARAN ANIMASI 2D KELAS XI ANIMASI SMK NEGERI 2 SURABAYA - Nur Isnaini Oktavia; Lamijan Hadi Susarno (Universitas Negeri Surabaya, 2023)
The purpose of developing game-based interactive multimedia media is to determine the feasibility of game-based interactive multimedia media to be presented in the subject matter of 2D animation work procedures and to determine the effectiveness of game-based interactive multimedia media in the learning process of 2D animation work procedure material for Class XI Animation at SMKN 2 Surabaya . The development model used is the ADDIE model with the subject of the XI Animation class XI Animation students at SMKN 2 Surabaya. Media feasibility data was obtained from the results of validation instruments from learning design experts, materials and media, as well as individual, small group and field product trials. Media effectiveness data obtained from the results of the pretest and posttest values that have been through the analysis of t test data. From the analysis of the t test data, the results obtained are t count 17.57 and t table 1.995 indicating t count is greater than t table. So, it can be concluded from the results obtained, showing game-based interactive multimedia media 2D animation work procedure material is feasible to be applied in learning activities 2D animation work procedure material and is effective in improving learning outcomes in class XI 2D animation work procedure material at SMKN 2 Surabaya